RANCANG BANGUN SARUNG TANGAN PINTAR PENERJEMAH BAHASA ISYARAT INDONESIA (BISINDO) BERBASIS IOT - wildana ahmad priadiyatna; Hudiono Hudino; Abdul Rasyid (Jurnal Jaringan Telekomunikasi, 2020)
To make the general public can understand sign language, people who translate sign language are needed. Research with titled "Design of Smart Gloves for Indonesian Sign Language Translator (BISINDO) based on IoT" purpose to make easier for deaf people communicate daily with general public. Using Esp-32 microcontroller, flex sensor, and gyroscope sensor, to detect hand movements form sign language symbols. The results of translating symbols in the words will be display on smartphone application. The results of this study are in the form of smart gloves that can translate Indonesian Sign Language which is abbreviated as BISINDO. From the data of both right and left hand gloves, 26 letters and 5 different words can be combined. The results of mapping on right glove in letters A, B, L, M, W, Y, Z, have almost same flex sensor angle value, so that characters can appear, the mapping is carried out on MPU-6050 sensor. Tests were carried out 739 times on letter sign symbols and 180 times on word sign language symbols, the percentage of successful experiments on letters was 95% and the percentage of successful experiments on words was 73%.